DnaC traps DnaB as an open ring and remodels the domain that binds primase. Issue 1 (29th September 2015) - Chodavarapu, Sundari; Jones, A. Daniel; Feig, Michael; Kaguni, Jon M.
Abstract : Helicase loading at a DNA replication origin often requires the dynamic interactions between the DNA helicase and an accessory protein. In E. coli, the DNA helicase is DnaB and DnaC is its loading partner. We used the method of hydrogen/deuterium exchange mass spectrometry to address the importance of DnaB–DnaC complex formation as a prerequisite for helicase loading. Our results show that the DnaB ring opens and closes, and that specific amino acids near the N-terminus of DnaC interact with a site in DnaB's C-terminal domain to trap it as an open ring. This event correlates with conformational changes of the RecA fold of DnaB that is involved in nucleotide binding, and of the AAA+ domain of DnaC. DnaC also causes an alteration of the helical hairpins in the N-terminal domain of DnaB, presumably occluding this region from interacting with primase. Hence, DnaC controls the access of DnaB by primase.